Channeling the Iron Ore Super-Cycle: The role of regional bank branch networks in emerging markets - Helge C. N. Littke (Leibniz-Institut für Wirtschaftsforschung Halle (IWH), 2018)
The role of the financial system to absorb and to intermediate commodity boom induced windfall gains efficiently presents one of the most pressing issues for developing economies. Using an exogenous increase in iron ore prices in March 2005, I analyse the role of regional bank branch networks in Brazil in reallocating capital from affected to non-affected regions. For the period from March 2004 to March 2006, I find that branches directly exposed to this shock by their geographical location experience an increase in deposit growth in the post-shock period relative to non-affected branches. Given that these deposits are not reinvested locally, I further show that branches located in the non-affected region increase lending growth depending on their indirect exposure to the booming regions via their branch network. Even tough, these results provide evidence against a Dutch Disease type crowding out of the non-iron ore sector, further evidence suggests that this capital reallocation is far from being optimal.
urn:nbn:de:gbv:3:2-93030
Keywords: G11; G21; O16; Q32; Q33; 330; banking; financial development; natural resources